Les parcs agroforestiers d’Azilal (Maroc) : une construction paysagère pluri-séculaire et toujours vivante - Aude Nuscia Taïbi; Mustapha El Hannani; Yahia El Khalki; Aziz Ballouche (Revue de Géographie Alpine)
The Moroccan Central High Atlas in the Beni Mellal - Khenifra region (Azilal Province) is characterized by highly anthropized landscapes as in all the medium mountain regions of Morocco. These are tree parks built by the rural Amazigh population in a context of rainfed food agriculture (bour), associated with extensive livestock farming, mainly sheep and goats. The very open landscapes are dominated by pre-forest formations of trees outside the forest (dominant holm oaks) selected in the fields. Dendrochronological analyses on holm oaks in the municipality of Agoudi N'Lkhir show that a large number of them are 200 to 300 years old and their regular treatment by long rotation (secular) grape varieties raises the structure of the tree park to at least 500 to 600 years. Despite this ancient historical foundation, these highly anthropized formations are often approached in terms of degradation, as are morphogenic processes, which are locally marked by strong erosion. However, field observations and diachronic analyses based on satellite images and aerial photographs show that these tree-lined parks, far from being relics of past landscapes, are still perennial and maintained by rural populations, as they continue to offer multiple vital functions and retain an important social role in these harsh and isolated mountainous contexts of the Moroccan Central High Atlas.